2019
DOI: 10.1371/journal.pgen.1008346
|View full text |Cite
|
Sign up to set email alerts
|

The (p)ppGpp-binding GTPase Era promotes rRNA processing and cold adaptation in Staphylococcus aureus

Abstract: Ribosome assembly cofactors are widely conserved across all domains of life. One such group, the ribosome-associated GTPases (RA-GTPase), act as molecular switches to coordinate ribosome assembly. We previously identified the Staphylococcus aureus RA-GTPase Era as a target for the stringent response alarmone (p)ppGpp, with binding leading to inhibition of GTPase activity. Era is highly conserved throughout the bacterial kingdom and is essential in many species, although the function of Era in ribosome assembly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…Studies in E. coli demonstrated its essentiality in the biogenesis of the 50S ribosomal subunit (56). In bacteria, the colocalization of ybeZ and ybeY in an operon is highly conserved (36)(37)(38). Here, we demonstrated the interaction between YbeY and YbeZ in P. aeruginosa and found that mutation of ybeZ resulted in similar phenotypes as the ybeY mutant.…”
Section: Figmentioning
confidence: 58%
See 1 more Smart Citation
“…Studies in E. coli demonstrated its essentiality in the biogenesis of the 50S ribosomal subunit (56). In bacteria, the colocalization of ybeZ and ybeY in an operon is highly conserved (36)(37)(38). Here, we demonstrated the interaction between YbeY and YbeZ in P. aeruginosa and found that mutation of ybeZ resulted in similar phenotypes as the ybeY mutant.…”
Section: Figmentioning
confidence: 58%
“…However, the mechanisms by which YbeY affects bacterial virulence and stress response remain unclear. Among bacterial species, including P. aeruginosa, E. coli, and Staphylococcus aureus, the ybeY gene is colocalized with a ybeZ gene in the same operon (36)(37)(38). In E. coli, YbeY has been found to interact with YbeZ (37), indicating a functional connection between the two proteins.…”
mentioning
confidence: 99%
“…Finally, we would like to draw the attention of the research community working on long RSH enzymes to technical aspects of protein purification. It is common to purify Rel/RelA for biochemical experiments using a single-step purification [for example (Wood et al, 2019)]. However, both RelA (Turnbull et al, 2019) and Rel have a strong tendency for RNA contamination and multiple additional steps are necessary to remove this contaminant.…”
Section: Discussionmentioning
confidence: 99%
“…Without extra steps to remove RNA contamination, single-step preparations are likely to be heavily contaminated with ribosomal particles (Figure 6), which is likely to interfere with the estimation of the oligomerization state of Rel, since the RNA-bound protein elutes much earlier than the RNA-free fraction (Figures 5B,C). This contamination may explain the surprising observation that the addition of Ni-NTA purified S. aureus Rel inhibits the 50S assembly factor DEAD-box RNA helicase CshA (Wood et al, 2019). The unlabeled contaminating ribosomal particles could potentially be recognized by CshA, thus acting as a competitor in the helicase assay that uses a synthetic Cy3-labeled RNA duplex as a substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation